“In the appropriate setting” - Dennis, Whitney (Acta historiae artis Slovenica, 2023)
This paper presents a comparison of the exhibition of art in the Duke of Alba’s original Liria Palace in 1931, which was destroyed in the Spanish Civil War in 1936, with a later exhibition in the reconstructed Liria Palace in 1957. It examines what is known of the original Liria Palace’s exhibition of art, as well as the history of those spaces, and compare it with the reconstructed Liria Palace. It also reflects on the significance of the role the art collection played in the reconstruction process. The exhibition of the Alba collection in the reconstructed Liria Palace formed part of the Duke’s strategies for perpetuating social distinction in the 20th century by preserving collective family memory, manifesting continuity, and imbuing the collection with unique meaning through the contextualization in this private setting.
Keywords: Alba (plemiška rodbina); art collecting; art collections; musealization; museugraphy; muzealizacija; muzeografija; nobility; plemstvo; Prado; Prado Museum; private collections; umetnostne zbirke; zasebne zbirke; zbirateljstvo